On Teaching Karl Rahner to Undergraduates - Peters, Carmichael C. (Philosophy & theology, 1998)
In teaching courses on Karl Rahner to undergraduates, I have come to appreciate the importance of finding a starting point with which students readily connect. After much thought, I begin these courses with an extended consideration of the human person. This starting point has the advantage not only of being Rahner’s but also of being one which seems attractive to students. I have found little evidence that students have to be convinced about the importance of self-concern. I am careful to emphasize, however, that in Rahner’s understanding of the dynamism of conversio and reditio this starting point never allows for any form of narcissistic subjectivism. Starting with the concreteness of our lives naturally leads to other considerations which also seem attractive to students: the burden of self-responsibility, the sense of awe and wonder, the need for hope. These are among some of the concerns which I try to address when teaching Rahner.